Penerapan Algoritma Sentimen Analysis dan Naïve Bayes terhadap opini pengunjung di tempat wisata pantai Pintu Kota, Kota Ambon - Julius Chrisostomus Aponno (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
In the current development of information technology, sentiment analysis is often used as a tool to seek public opinion about something. Naive Bayes analysis is a method of classifying data based on simple probabilities and is designed to be used with the assumption that there is no interdependence between one class and another. The purpose of this study was to determine public opinion about visitor satisfaction at Pintu Kota Ambon by testing positive and negative recall values, as well as positive and negative precision values ​​and accuracy values ​​using sentiment analysis and naive Bayes analysis. All data are processed using RapidMiner tools. In this survey, we obtained data from the results of the search for comments from visitors to the Pintu Kota Ambon attraction on the Google Maps website. The results obtained from this study indicate that the tracking of sentiment analysis and Naive Bayes analysis of the opinions of 113 visitors showed a negative recall value of 97.62% and a negative recall value of 83.33%.The negative accuracy value is 85.42%, while the positive accuracy value is 97.22% From these results obtained an accuracy value of 90.65%.From the results of the analysis, tourist destinations at Ambon City Gate are considered good because they get a high accurate value of 90.65%. From this research, it can be concluded that it is necessary to develop an information system to track visitor satisfaction in other tourist destinations.